1999
DOI: 10.1016/s0002-9440(10)65285-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcomas Express Mixed Endothelial Phenotypes of Blood and Lymphatic Capillaries

Abstract: Angiosarcomas apparently derive from blood vessel endothelial cells; however, occasionally their histological features suggest mixed origin from blood and lymphatic endothelia. In the absence of specific positive markers for lymphatic endothelia the precise distinction between these components has not been possible. Here we provide evidence by light and electron microscopic immunohistochemistry that podoplanin, a approximately 38-kd membrane glycoprotein of podocytes, is specifically expressed in the endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
720
1
14

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 963 publications
(763 citation statements)
references
References 20 publications
14
720
1
14
Order By: Relevance
“…Recently, podoplanin, an B38 kDa membrane mucoprotein originally detected on the surface of rat podocytes, 13 was established as a specific marker for lymphatic endothelium. 23 This discovery changed the landscape for lymphatic studies, with podoplanin being used as a valuable marker for identifying lymph vessels and accurately evaluating lymph vessel density. 17,18,[24][25][26] In this study, we found that lymph node metastasis was statistically correlated with both increased lymph vessel density and VEGF-D expression of both mRNA and protein, and that VEGF-D immunoreactivity was significantly and positively correlated with increased lymph vessel density.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, podoplanin, an B38 kDa membrane mucoprotein originally detected on the surface of rat podocytes, 13 was established as a specific marker for lymphatic endothelium. 23 This discovery changed the landscape for lymphatic studies, with podoplanin being used as a valuable marker for identifying lymph vessels and accurately evaluating lymph vessel density. 17,18,[24][25][26] In this study, we found that lymph node metastasis was statistically correlated with both increased lymph vessel density and VEGF-D expression of both mRNA and protein, and that VEGF-D immunoreactivity was significantly and positively correlated with increased lymph vessel density.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular domain is highly O-glycosylated, with sialic acid, a-2,3 linked to galactose, forming the main part of the protein's carbohydrate moieties. In normal human tissue, podoplanin is expressed in kidney podocytes (Breiteneder-Geleff et al, 1999), in skeletal muscle, placenta, lung and heart (Martin-Villar et al, 2005), in myofibroblasts of the breast and salivary glands, in osteoblasts and mesothelial cells (Ordonez, 2006b). It is also expressed on the apical surface of rat alveolar type I cells (Rishi et al, 1995).…”
Section: Podoplanin Is Expressed In Most Human Tissuesmentioning
confidence: 99%
“…Podoplanin is highly and specifically expressed in lymphatic endothelial cells, but not in blood vessel endothelium. 4,5 It has been shown that podoplanin deficiency disrupts normal lymphatic vasculature formation. As podoplanin is expressed on lymphatic but not on blood vessel endothelium, it is widely used as a specific marker for lymphatic endothelial cells and lymphangiogenesis in many species.…”
mentioning
confidence: 99%